Comparative awareness on zoonoses between residents at the Human-wildlife Interface Zone and inhabitants of the non-wildlife areas of Meru County, Kenya - M'ibui, Gervase; Karani, Caroline K.; Nkonge, Ananias N.; Ireri, Edward M. (African Journal of Science, Technology and Social Sciences, 2024)
Abstract Introduction: Zoonoses are infections transmitted from vertebrate animals to humans. Persons with low knowledge, exposure to wildlife or domestic animals are at risk of zoonoses. Research, surveillance and response through One Health framework is necessary for prevention. We compared the knowledge on zoonoses between residents at the wildlife-interface of Meru National Park, and non-wildlife areas of Tigania West Sub County, Meru Kenya. Methods: Data were simultaneously collected using a structured questionnaire in both zones and compared. Descriptive statistics were used to summarize the data for differences between variables in the two areas. Results: The non-wildlife zone residents of Tigania West Sub-County had statistically significantly better knowledge of zoonoses than their counterparts next to Meru National Park: χ² (1, N=525) =84.965, p< .001. Conclusion: The scanty knowledge on zoonoses of residents of Igembe Central posed greater risk of zoonoses because their proximity to the wildlife conservancy. Awareness creation through one health strategy is necessary as a deterrent measure.